Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3390/en11030683
|View full text |Cite
|
Sign up to set email alerts
|

Big Data Analytics for Discovering Electricity Consumption Patterns in Smart Cities

Abstract: New technologies such as sensor networks have been incorporated into the management of buildings for organizations and cities. Sensor networks have led to an exponential increase in the volume of data available in recent years, which can be used to extract consumption patterns for the purposes of energy and monetary savings. For this reason, new approaches and strategies are needed to analyze information in big data environments. This paper proposes a methodology to extract electric energy consumption patterns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(61 citation statements)
references
References 31 publications
(26 reference statements)
0
61
0
Order By: Relevance
“…[35][36][37] The notion of connected vehicles can be beneficial to save energy inside the EVs, and several test and discussion in relation were exposed in the previous studies. 2,38,39 As the new commercialized vehicles were equipped with a wireless communication system, each vehicle can be proactive, cooperative, well-informed, and coordinated and will pave the way for supporting various applications for road safety. [40][41][42] Therefore, it is possible to guarantee, vehicle to building communication (V2B), or vehicle to road infrastructure communication (V2I) this characterizes the vehicle to the smart city connection.…”
Section: Buildings Infrastructures and Electric Vehicle Relationshipmentioning
confidence: 99%
See 2 more Smart Citations
“…[35][36][37] The notion of connected vehicles can be beneficial to save energy inside the EVs, and several test and discussion in relation were exposed in the previous studies. 2,38,39 As the new commercialized vehicles were equipped with a wireless communication system, each vehicle can be proactive, cooperative, well-informed, and coordinated and will pave the way for supporting various applications for road safety. [40][41][42] Therefore, it is possible to guarantee, vehicle to building communication (V2B), or vehicle to road infrastructure communication (V2I) this characterizes the vehicle to the smart city connection.…”
Section: Buildings Infrastructures and Electric Vehicle Relationshipmentioning
confidence: 99%
“…Effectively, several types of researches proved that a smart city will encourage using the electrical transportation systems, as electric cars and electric buses, in which the problems related to the high recharge delay will be eliminated in the future . The notion of connected vehicles can be beneficial to save energy inside the EVs, and several test and discussion in relation were exposed in the previous studies …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examining the papers selected and summarized in Table S15, presented in the Supplementary Materials file, it can be observed that 67% of them take into consideration smart buildings in general, while the remaining 33% refer to smart homes. The authors of these scientific articles made use of different types of sensors in their analyses, including binary sensors [26]; sensor networks [140]; smart meters, Personal Weather Stations (PWS), and sensors providing data useful in computing the mean values of: hourly indoor temperature, hourly outdoor temperature, hourly value of precipitation, hourly value of wind direction, hourly value of solar radiation, hourly value of ultraviolet index, hourly value of humidity, hourly value of pressure [42]. In these papers, the reasons for using the K-Means method with the sensor devices in smart buildings were related to extraction of behavioral patterns [26]; determining electricity consumption patterns [140]; and managing energy consumption [42].…”
Section: Unsupervised Learningmentioning
confidence: 99%
“…Unsupervised techniques have also been used to discover relevant patterns within consumption time series. In particular, data from a Spanish public university were analyzed in [5] in order to discover load profiles and reduce costs. Similar strategies were applied to determine whether Polish customers choose proper tariffs or not in [6].…”
mentioning
confidence: 99%